Breaking the poverty cycle: the human basis for sustainable development - Pick, Susan; Sirkin, Jenna (New York, 2010)
"The book shows how community development can be enhanced if people are enabled to make accountable choices and expand their alternatives. International development efforts will not be sustainable if we continue to build schools without quality teachers; health clinics without enhancing logistical and psychological access and improving quality of care; and laws that are not enforced. Institutions will only flourish if their leaders and bureaucrats enhance their personal capabilities. The central premise of the book is that enhancing skills, knowledge and reducing psychological and contextual barriers to change are central (and often neglected) aspects of sustainable development."